Роль нейровоспаления в механизмах гибели нигростриатных дофаминергических нейронов при болезни Паркинсона - Kucheryanu, V. G.; Voronina, N. A.; Bocharov, E. V.; Vetrile, L. A.; Goloborshcheva, V. V.; Bocharova, O. A.; Davydova, T. V.; Gruden, M. A.; Sewell, R. D.; Kapitsa, I. G.; Voronina, T. A. (Патогенез, 2022)
Тезисы конференции